Effects of the Learning how to motivate training on pupils’ motivation and engagement during pre-service physical education teachers’ internship - Girard, Stéphanie; de Guise, Audrey-Anne (Frontiers in Education, 2024)
IntroductionPre-service physical education (PE) teachers have concerns about how to sustain pupils’ motivation. A training titled Learning how to motivate was designed to address these concerns.ObjectivesThe aims of the study were (1) to compare the perceptions of high school pupils of pre-service PE teachers who had completed the training [experimental group (EG)] and pre-service PE teachers who had not completed the training [control group (CG)] about motivation; (2) to verify changes in the perceptions of EG and CG high school pupils with regard to motivational variables between the beginning and end of the internship; and (3) to compare observations of the motivational climate established by the pre-service PE teachers and of their pupils’ engagement between EG and CG.MethodsThe study involves a sample of four French-Canadian pre-service PE teachers (EG = 2; CG = 2) and their high school pupils (n = 89) during the pre-service PE teachers’ final internship. Data were collected using observations and questionnaires at the start (T1) and end (T2) of the internship.ResultsFindings revealed no significant differences between groups at T1. At T2, the EG exhibited higher levels of pupils’ perceived dimensions of an empowering motivational climate than the CG. Notably, between T1 and T2, performance-approach goals decreased, and external regulation increased in the EG. As for the CG, pupils’ perceived dimensions of an empowering motivational climate, competence satisfaction, and performance-approach goals decreased. Finally, there were some trends (p ≤ 0.15) related to differences between the groups for observed motivational climate and pupils’ engagement.ConclusionThe training shows promise with regard to helping pre-service PE teachers apply theory to practice.